Permeability and Diffusivity Measurements on Polymer Electrolyte Membranes1. Issue 1 (19th December 2012) - Arena, F.; Mitzel, J.; Hempelmann, R.; Di Vona, Maria Luisa; Knauth, Philippe; Rozière, Jacques; Norby, Truls
Abstract An essential material property directly influencing the long‐life capacity of hydrogen‐polymer electrolyte membrane fuel cells (H2‐PEMFCs) systems at elevated temperatures (>80 °C) is the permeability of the PEM material toward gases. The membrane permeability with respect to hydrogen and oxygen is responsible for a decrease of fuel cell efficiency and life‐time. Furthermore permeating oxygen is suspected to form membrane degrading O‐radical species. In view of the importance of gas permeability for further PEM R&D activities we present a test bench for the experimental determination of gas diffusivities and permeabilities for such polymeric materials. The advantages of a direct coupling of the permeation measurement cell with a gas chromatograph as analyzer are outlined. Hydrogen and oxygen diffusivities as well as permeabilities of prospective new materials such as cross‐linked SPEEK are determined at different temperatures and are compared to state‐of‐the‐art PFSA material. A significantly lower permeability regarding hydrogen and oxygen was determined for cross‐linked SPEEK materials. In addition the influence of the hydro‐thermal history of PFSA materials, postulated by G. Alberti, on membrane diffusivity was studied.